Effect of endomorphins on humoral immune response, Th1/Th2/Th17 cytokine production and CD4+, CD8+ lymphocyte apoptosis in vivo - Ya. A. Kadochnikova; S. V. Gein (Медицинская иммунология)
Endogenous opioid peptides are a large group of physiologically active compounds with a pronounced affinity for opioid-type receptors, capable of showing pronounced analgesic activity, as well as having additional effects on the periphery, due to their wide distribution on the cells of many organs and tissues. Little studied representatives of this group are endomorphins, which due to their structure and properties, are capable of producing a strong antinociceptive effect after central administration, which means that, in the future, they can be considered as potential substitutes for low molecular weight opiates. The aim of this study is to evaluate the effect of endomorphins on the humoral immune response, the production of Th1/Th2/Th17 cytokines and apoptosis of CD4+, CD8+ lymphocytes in vivo. The splenocytes of Swiss white mice were used as the object of the study. The number of antibody-forming cells in the spleen was assessed using the method of local hemolysis in agarose gel according to Jerne. Quantitative determination of cytokines was carried out by enzyme-linked immunosorbent assay using kits (R&D, USA) according to the method proposed by the manufacturer. Apoptosis was assessed using Annexin V-FITC/7-AAD kit reagents (Beckman Coulter, USA) according to the manufacturer’s instructions by flow cytometry on a CytoFLEX S flow cytometer (Beckman Coulter, USA). In the course of the study, it was found that endomorphins enhance the antibody genesis of the spleen, and the preliminary blockade of opiate receptors with naloxone led to the cancellation of the stimulating effect of peptides. Endomorphins didn’t affect splenocyte production of IL-2, IL-4, and IFNg, however, the introduction of endomorphin-2 naloxone-independent enhanced the induced production of IL-17. Evaluation of the effect of endomorphins on apoptosis of splenocytes in 24-h cultures showed that endomorphin-2 in unstimulated cultures of naloxone-dependently increased the percentage of late apoptosis of CD8+ lymphocytes, however, in stimulated cultures, both endomorphins increased the apoptotic activity of CD8+ lymphocytes, regardless of the preliminary blockade of opioid receptors. In summary, we can say that in the in vivo system, endomorphins have a wide range of multidirectional immunomodulatory effects, which may be of interest for practical use in the future.